Aplikasi Verticillium Lecaniizim. Isolat Palolo terhadap Kutu Putih (Bemisia Tabaci Genn.) (Hemiptera:Aleyrodidae) Pada Tanaman Tomat - Nurdahlia Nurdahlia; Alam Anshary; Hasriyanty Hasriyanty (Agroland: Jurnal Ilmu-ilmu Pertanian, 2018)
One of the common insects that attack tomato plant is whitefly (Bemisiatabaci Genn.). One of those classified as entomopatogen is Verticillium lecanii. The purpose of this study was to determine the effect of V. lecaniispore density on B. tabaci mortality in tomato plants. The study was conducted from January to April 2017 and located in a screening house belonging to the Department of Plant Pest and Disease and Plant Pest and Disease Laboratory, Faculty of Agriculture, Tadulako University. This study used a randomized block design consisting of five treatments including control with three replications so that there are 15 experimental units. The spore density ofV. lecanii consisted of five levels i.e. control (without treatment, p0), 10-3 Spores ml-1 (p1), 10-6 Spores ml-1 (p2),10-9 Spores ml-1(p3) and 10-12 Spores ml-1 (p4). Based on the results of the study, 10-3Spores ml-1 was the spore density that caused the highest mortality of B. tabaci with the mortality of 96.67% within eight days after the application, so the use of V. lecanii was quite effective as a bioinsecticide in controlling imago B. tabaci.